Nyadran Semiotics and the Negotiation of Culture and Religion: A Pre-Ramadan Javanese Ritual in Kuncen Village, Karangduren, Tengaran, Semarang Regency - Nur Fadilah (Journal of Nahdlatul Ulama Studies, 2024)
Nyadran is a Javanese ritual tradition commonly performed prior to Ramadan through a sequence of grave cleaning (besik kubur), cemetery visitation (nyekar/ziarah), collective prayers and tahlil, and communal feasting (kenduri/manganan). This tradition merits scholarly attention because it reveals a dynamic encounter among local cultural memory, Islamic piety, and social cohesion amid the growing discourse of religious purification. The research questions are: (1) how the Nyadran procession in Kuncen Hamlet (Karangduren, Tengaran, Semarang) is carried out before Ramadan, (2) how ritual signs (objects, actions, utterances, and spatio-temporal arrangements) are interpreted by residents, and (3) how Nyadran functions socio-religiously as an arena for negotiating local tradition and Islamic devotion. This study employs a qualitative–interpretive approach with a case study design. Data were collected through participant observation across the Nyadran sequence, in-depth interviews with hamlet elders, the rois (local religious authority)/religious figures, organizing committee members, and residents, as well as document analysis for triangulation. The data were then analyzed thematically and interpretively using a semiotic ritual lens (Peircean–Barthesian semiotics and Turner–Bell ritual theory) to map sign object interpretant relations and examine processes of ritualization, liminality, and the formation of communitas. The findings show that Nyadran in Kuncen is not a mere “remnant of tradition,” but a signifying system that produces the meaning of “cleanliness” (physical–spiritual–social) as readiness for Ramadan. Signs such as mixed flowers, incense, apem–ketan–kolak, tumpeng/ingkung, communal kenduri, and the timing in Ruwah/Sya’ban function as symbolic communication devices that affirm gratitude, filial piety toward ancestors/parents, moral discipline, and communal solidarity, while also demonstrating the recontextualization of ancestral remembrance into Islamic devotional repertoires (tahlil, supplication, and almsgiving). Nyadran thus operates as an adaptive form of vernacular Islam. Recommendations include community-based documentation (audio-visual and written archives), strengthening inclusive religio-cultural literacy to explain symbolic meanings and normative boundaries, engaging youth and schools to use Nyadran as a medium for character education without imposing interpretive uniformity, sustainable governance (transparent contributions, waste management, and environmentally responsible cemetery arrangements), and further comparative cross-village studies as well as analyses of changing religious discourses and their effects on Nyadran practices.